2009
DOI: 10.1523/jneurosci.1042-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

TRPC Channels Mediate a Muscarinic Receptor-Induced Afterdepolarization in Cerebral Cortex

Abstract: Activation of muscarinic cholinergic receptors on pyramidal cells of the cerebral cortex induces the appearance of a slow afterdepolarization that can sustain autonomous spiking after a brief excitatory stimulus. Accordingly, this phenomenon has been hypothesized to allow for the transient storage of memory traces in neuronal networks. Here we investigated the molecular basis underlying the muscarinic receptor-induced afterdepolarization using molecular biological and electrophysiological strategies. We find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(147 citation statements)
references
References 54 publications
(118 reference statements)
9
133
0
Order By: Relevance
“…At the cellular level, activation of m1 AChR results in a plateau potential similar to the one induced by activation of mGluRs. Although several studies have suggested that this plateau potential may be mediated by neuronal TRPC channels (Yan et al, 2009;Zhang et al, 2011;Tai et al, 2011), knocking out both TRPC1 and TRPC4, two highly expressed TRPCs, did not diminish the severity of pilocarpine-induced seizures (Phelan et al, 2012). This result suggests that heteromeric TRPC1/4 channels are not required for pilocarpineinduced seizures; however, TRPC5-containing channels could still be required.…”
Section: And E)mentioning
confidence: 82%
See 1 more Smart Citation
“…At the cellular level, activation of m1 AChR results in a plateau potential similar to the one induced by activation of mGluRs. Although several studies have suggested that this plateau potential may be mediated by neuronal TRPC channels (Yan et al, 2009;Zhang et al, 2011;Tai et al, 2011), knocking out both TRPC1 and TRPC4, two highly expressed TRPCs, did not diminish the severity of pilocarpine-induced seizures (Phelan et al, 2012). This result suggests that heteromeric TRPC1/4 channels are not required for pilocarpineinduced seizures; however, TRPC5-containing channels could still be required.…”
Section: And E)mentioning
confidence: 82%
“…The contribution of excitatory synaptic input and intrinsic membrane properties to the plateau potential has been long debated. Three candidates remain in contention as the ion channels that mediate the plateau potential underlying the epileptiform bursts: persistent Na 1 channels with uncertain molecular identity (Chen et al, 2011), T-type voltage-gated Ca 21 channels (Cain & Snutch, 2010), and TRPC channels (Gee et al, 2003;Wang et al, 2007;Yan et al, 2009;Phelan et al, 2012).…”
Section: And E)mentioning
confidence: 99%
“…S5 B, D, available at www.jneurosci.org as supplemental material), suggesting that the high responsiveness of O-LM cells to mAChR activation is largely mediated by M 3 rather than M 1 . Recently, it has been shown in cortical pyramidal cells that transient receptor potential canonical (TRPC) is the molecular basis of mAChRinduced G␣ q/11 /phospholipase C␤1-mediated afterdepolarization (Yan et al, 2009). Therefore, although it remains to be tested whether this is also the case in the O-LM cells, it is also possible to assume that O-LM cells may particularly develop mechanisms that could facilitate or magnify functional linkage between mAChR and downstream effectors compared with other classes of cortical interneurons.…”
Section: Is Scarce In Cortical Gabaergic Interneuronsmentioning
confidence: 99%
“…Five subtypes of mAChRs have been identified and classified into two subfamilies: the M 1 -like subfamily (M 1 , M 3 , and M 5 ) is coupled to G␣ q/11 protein, leading to activation of phospholipase C, whereas the M 2 -like subfamily (M 2 and M 4 ) is coupled to G i/o , which inhibits adenylate cyclase . In general, mAChR activation modulates multiple ionic conductances and depolarizes cortical pyramidal cells, thereby enhancing the generation and backpropagation of action potential (Krnjevic et al, 1971;McCormick and Prince, 1985;Tsubokawa and Ross, 1997;Gulledge and Stuart, 2005;Gulledge et al, 2009;Yan et al, 2009). Furthermore, mAChR activation induces network oscillations (Fisahn et al, 1998(Fisahn et al, , 2002Traub et al, 2004), and modulates the induction and amplitude of long-term potentiation (LTP) at hippocampal synapses (Huerta and Lisman, 1993;Shinoe et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we examined whether channel modulations driven by other PLC-coupled receptors are also Ca 2+ dependent. We found that the activation of I-mGluRs, like muscarinic activation, induced the activation of NSC-like channels and inhibition of K + channels, and that these Many studies have shown the Ca 2+ -dependent property of NSC channel activation (Blair et al, 2009;Congar et al, 1997;Fraser and MacVicar, 1996;Gee et al, 2003;Magistretti et al, 2004;Yan et al, 2009;Zhang et al, 2011), and it has been mostly interpreted as the Ca 2+ dependence of NSC channel itself. Our data do not negate the Ca 2+ dependence of NSC channel itself, but suggest that caution must be exercised in interpreting experimental data (Blair et al, 2009).…”
Section: Discussionmentioning
confidence: 86%